PRODUKTIVITAS KERJA DITINJAU DARI KEPEMIMPINAN DAN MOTIVASI KERJA PADA PEKERJA BAGIAN PRODUKSI PT. X DI CILACAP (Studi Kasus di Kabupaten Cilacap) - , SAMOSIR ROMA ULI PURBA, Prof. Dr. dr. Adi Heru Sutomo, M.Sc., D.Comm., DPLTM, PKK ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Workers are one of the most important element that determines whether or not organizations succeed and achieve goals and to develop its mission. Leaders have an important role in improving employee productivity. In addition to that, employees must also have a high motivation to be productive in their works. Objective: This study aims to determine the relationship between leadership and motivation to work with labor productivity as well as the leadership of the workers motivation to work on the production of PT. X in Cilacap. Methods: This research used descriptive analytical method. The population of this research was the employee who were work in the production section. The number of sample research were 88 people taken using simple random sampling technique. The analysis used were univariate and multivariate statistical analysis with multiple regression tests. Results: There was a positive relationship between leadership and productivity of employee working on the production of PT. X. The great number on the effect of leadership on the labor productivity was to 31.10%. There is a positive relationship between motivation on work with labor productivity in the production section of PT. X. The great number of the influence of motivation on work on workers productivity by 38.80%. There is a positive relationship between leadership and employee motivation to work in the production of PT. X. The great number of the effect of leadership on the motivation of 12.70%. There is a positive relationship between leadership and motivation on work on workers productivity in the production of PT. X. The great number of the effect of leadership and motivation to work with productivity by 51.70%. Conclusion: Leadership and motivation have positive relation to labor productivity. Leadership have positive relation to motivation to work.